Synthesis and Properties of Linear Polyether-Blocked Amino Silicone-Modified Cationic Waterborne Polyurethane. (8th April 2020) - Xu, Chengshu; OuYang, Lei; Ren, Yan; Cai, Zaisheng; Lu, Shaofeng; Zhang, Jing; Shi, Wenzhao
Abstract : In this study, a waterborne polyurethane (WPU) is synthesized by using polytetramethylene ether glycol (PTMEG) to form the soft segment, 1, 4-butanediol (BDO) as the chain extender, n-methyldiethanolamine (MDEA) as a hydrophilic chain extender, and isophorone diisocyanate (IPDI) to form the hard segment. Furthermore, the modified cationic WPU emulsion and its films are created through a reaction between the WPU and a linear polyether-blocked amino silicone (LEPS), which is an organosilicon compound that imparts flexibility. The properties of the structure and formed WPU films are then characterized by using Fourier transform infrared spectrometry, a thermogravimetric analysis, atomic force microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy, as well as by measuring the water contact angle, testing the water absorption, etc. It is found that, with an increase in the LEPS content in the WPU, the particle size of the modified WPU emulsion is increased, the WPU films are more flexible, and the resistance of the modified WPU films to heat and water are increased, while the crystallinity is reduced. The polysiloxane chain segment, which is added to the LEPS-modified WPU emulsion, is significantly enriched on the surface of the modified WPU films, while there are no adverse effects of the LEPS-modified WPU emulsion on the adhesive force between the WPU and substrate. When the LEPS content of the WPU is 14.0 wt%, the modified WPU emulsion and film provide the best performance.